(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
The mutagenic and clastogenic action of the waters of three bore holes and of the three artificial fish reservoirs in Armavir marz was investigated by Tradescantia (clone 02) somatic mutation hairs (Trad-SH) and micronucleus (TradMN) test-systems. It was revealed, that from 6 samples more genotoxic were the water samples taken from Aknashen bore-hole and Aknashen fish reservoir.